Favourable outcome of progressive multifocal leucoencephalopathy in two patients with dermatomyositis. Issue 9 (16th August 2006) - Vulliemoz, S; Lurati-Ruiz, F; Borruat, F-X; Delavelle, J; Koralnik, I J; Kuntzer, T; Bogousslavsky, J; Picard, F; Landis, T; Du Pasquier, R A
Abstract : Progressive multifocal leucoencephalopathy (PML), a demyelinating disease caused by the JC virus (JCV), occurs in immunosuppressed patients and carries a poor prognosis. A favourable outcome is reported in two patients with PML and dermatomyositis. Immunosuppressive drugs were stopped in patient 1 but could only be partially tapered in patient 2. The JCV-specific CD8+ T cell response was strong in patient 1 and weak in patient 2. Both were treated with cytosine-arabinoside, and patient 2 was also treated with mirtazapine, a 5HT2A receptor antagonist. Combination of these drugs might be helpful to treat HIV-negative patients with PML.